Autoinflation for hearing loss associated with otitis media with effusion. - Perera, R; Glasziou, P; Heneghan, C; McLellan, J; Williamson, I (2013)
This is an update of a Cochrane review first published in The Cochrane Library in Issue 4, 2006.Otitis media with effusion (OME) or 'glue ear' is an accumulation of fluid in the middle ear, in the absence of acute inflammation or infection. It is the commonest cause of acquired hearing loss in childhood and the usual reason for insertion of 'grommets'. Potential treatments include decongestants, mucolytics, steroids, antihistamines and antibiotics. Autoinflation devices have been proposed as a simple mechanical means of improving 'glue ear'. To assess the effectiveness of autoinflation compared with no treatment in children and adults with otitis media with effusion. We searched the Cochrane Ear, Nose and Throat Disorders Group Trials Register; the Cochrane Central Register of Controlled Trials (CENTRAL); PubMed; EMBASE; CINAHL; Web of Science; BIOSIS Previews; Cambridge Scientific Abstracts; ICTRP and additional sources for published and unpublished trials. The date of the most recent search was 12 April 2013. We selected randomised controlled trials that compared any form of autoinflation to no autoinflation in individuals with 'glue ear'. Two review authors independently assessed studies for inclusion, assessed risk of bias and extracted data from included studies. Eight studies, with a total of 702 participants, met the inclusion criteria. Overall, the studies were predominantly assessed as being at low or unclear risk of bias; unclear risk was mainly due lack of information. There was no evidence of selective reporting.Pooled estimates favoured the intervention, but did not show a significant effect on tympanometry (type C2 and B) at less than one month, nor at more than one month. Similarly, there were no significant changes for discrete pure-tone audiometry and non-discrete audiometry. Pooled estimates favoured, but not significantly, the intervention for the composite measure of tympanogram or audiometry at less than one month; at more than one month the result became significant (RRI 1.74, 95% CI 1.22 to 2.50). Subgroup analysis based on the type of intervention showed a significant effect using a Politzer device under one month (RRI 7.07, 95% CI 3.70 to 13.51) and over one month (RRI 2.25, 95% CI 1.67 to 3.04).None of the studies demonstrated a significant difference in the incidence of side effects between interventions. All of the studies were small, of limited treatment duration and had short follow-up. However, because of the low cost and absence of adverse effects it is reasonable to consider autoinflation whilst awaiting natural resolution of otitis media with effusion. Primary care could prove a beneficial place to evaluate such interventions and there is ongoing research in this area. Further research should also consider the duration of treatment, the long-term impact on developmental outcomes in children and additional quality of life outcome measures for children and families.